Carte reduite du Grand Banc et d'une partie de l'Isle de Terre Neuve - Bellin, Jacques Nicolas, 1703-1772 (Paris, 1764)
Black and white. Prime meridian Paris. Rhumb lines. Decorative title cartouche. Relief shown pictorially. Depths shown by soundings. Bar scale in French and English marine leagues.